PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KUALITAS KERJA GURU SEKOLAH MENENGAH ATAS SWASTA ZONA I JAKARTA UTARA - Zubel Purba (Jurnal Manajemen Pendidikan, 2018)
The purpose of this research is to know the effect of transformational leadership and work environment toward teacher’s job quality private senior high school north of Jakarta. The research was conducted using survey method with quantitative approach and path analysis technique. The population of this research is 117 teachers. Research samples selected as much as 91 teachers using simple random sampling technique. The data obtained through questionnaires and analyzed using path analysis techniques. Based on the results of data analysis in this research it is concluded: (1) the transformational leadership have positive direct effect to job quality; (2) the work environment have positive direct effect to job quality; (3) the transformational leadership have positive direct effect to work environment. The job quality can be improved through improvement of of transformational leadership and work environment.